Vestibular Physiotherapy and Yoga in Vasovagal Syndrome: case report (Research, Society and Development, 2021)
This study aimed to report the effects of vestibular physiotherapy (VP) associated with Yoga in a vasovagal syndrome (VVS) patient with dizziness and body imbalance complaints. We described a 22-year-old patient who underwent one year of VP with a frequency of one to two times per week (totaling 31 sessions). The treatment for the cervical region was performed using manual therapy and motor control training of the deep cervical flexor muscles. The patient started to practice Yoga three months after the beginning of the VP. After one year of treatment, a substantial improvement in the symptoms of dizziness and postural balance were observed. However, the cervical pain remained present and cervical mobility was slightly limited after two years. These findings lasted one year after the end of the VP program, a period in which the patient performed only Yoga. Despite the promising results, future studies with larger sample sizes and adequate methodological quality are necessary to confirm the effects of therapeutic exercises in individuals with VVS.